1993
DOI: 10.1097/00006254-199307000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcome in Pregnancy Following Amniotic Fluid Isolation of Ureaplasma urealyticum

Abstract: Infections in pregnancy with Ureaplasma urealyticum have been associated with a wide range of adverse outcomes, such as early abortion, stillbirth, prematurity, and neonatal morbidity and mortality. Causality has been difficult to demonstrate secondary to the high prevalence of asymptomatic lower genital tract (LGT) colonization and culture data from inaccessible or potentially contaminated sites.Between 1985 and 1989,2461 second-trimester genetic amniocenteses were evaluated at the cytogenetics section of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 12 publications
(15 reference statements)
4
77
0
3
Order By: Relevance
“…has been detected in some samples of amniotic fluid obtained in routine chromosomal analysis at 15-18 wk of gestation. In most of these women, delivery was around 24 wk (31)(32)(33). Meanwhile, Perni et al (34) reported that in 179 asymptomatic women who received amniocentesis at midtrimester, all women with preterm PROM (5/5) tested positive for either Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…has been detected in some samples of amniotic fluid obtained in routine chromosomal analysis at 15-18 wk of gestation. In most of these women, delivery was around 24 wk (31)(32)(33). Meanwhile, Perni et al (34) reported that in 179 asymptomatic women who received amniocentesis at midtrimester, all women with preterm PROM (5/5) tested positive for either Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…The AF concentrations of IL-8, MMP-8, and CRP were higher in the first twin, and this difference remained significant after adjustment for the fetal growth restriction at the time of birth and chorionicity. We included only twin pregnant women who delivered at term, because intra-amniotic infection and/or inflammation in midtrimester amniotic fluid itself is associated with an increased risk of preterm delivery [32][33][34][35][36].…”
Section: Different Respiratory Morbidity In Twin Pairsmentioning
confidence: 99%
“…colonize the lower genitourinary tract in 40 to 80% of sexually active women (11). These organisms have been implicated as etiologic agents causing nongonococcal urethritis, stillbirth/premature delivery, postpartum bacteremia, and wound infection post-caesarean section (3,7,12,13). They have also been associated with the development of neonatal pneumonia, meningitis, and chronic lung disease (8, 11, 17).…”
Section: Ureaplasma Parvum Belongs To the Class Mollicutesmentioning
confidence: 99%